The Therapeutic Potential of Exogenous Adenosine Triphosphate (ATP) for Cartilage Tissue Engineering - Usprech, Jenna (Cartilage, 2012)
OBJECTIVE: While mechanical stimuli can be used to enhance the properties of engineered cartilage, a promising alternative may be to directly harness the underlying mechanotransduction pathways responsible. Our initial studies on the adenosine triphosphate (ATP)–purinergic receptor pathway demonstrated that stimulation by exogenous ATP improved tissue growth and properties but elicited matrix turnover under high doses (250 µM) potentially due to the accumulation of extracellular inorganic pyrophosphate (ePPi). Therefore, the purpose of this study was to identify the mechanism of ATP-mediated catabolism and determine a therapeutic dose to maximize the anabolic effect. DESIGN: Isolated bovine articular chondrocytes were seeded in high-density, 3-dimensional culture supplemented with varying doses of ATP for 4 weeks. The effects on biosynthesis, matrix metalloproteinase 13 (MMP-13) protein activity, and PPi accumulation were determined. Separate monolayer experiments were conducted to determine the effect of ePPi on MMP-13 activity. RESULTS: High doses of ATP resulted in an increase in ePPi accumulation (by 54%) and MMP-13 activity (by 39%). Monolayer experiments confirmed a link between increased ePPi accumulation and MMP-13 activity, which appeared to require calcium and was inhibited by the MEK1/2 inhibitor U0126. Cultures supplemented with 62.5 to 125 µM ATP favored an anabolic response, which represented the therapeutic dose range. CONCLUSIONS: A therapeutic dose range of exogenous ATP to improve the properties of engineered cartilage has been identified, and a possible catabolic mechanism involving excess PPi was determined. Future research into PPi signal transduction and pathological crystal formation is necessary to maximize the beneficial effect of exogenous ATP on chondrocyte cultures.